The Effects of Preeclampsia On The Enzymatic Activity Of Full Term Placentae:Histochemical Study - Al-Sammak, Maha A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: This study is concerned with the effects of preeclampsia on the availability of the important enzymes in the full term placenta.For this purpose 2 groups of placentae were taken from the full term pregnant women immediately after labour, each group consists of 10 placentae, the first group are those placentae obtained from pregnant women having uneventful pregnancy with no history of any disease or complication (as a control group) while the second group includes those pregnant women having a history of preeclampsia, the results showed significant histochemical changes in the placentae of the second group when compared with the first group, such changes result from syncytial damage and destruction affecting the preeclamptic placentae of the second group, thus loss of alkaline phosphatase enzyme with increase in the amount of the degenerating acid phosphatase enzyme were observed in the placentae obtained from the preeclamptic group. the placentae have been implicated in the pathophysiology of preeclampsia. Patients & Methods: The specimens were obtained from Al-Batool & Al-Khansaa Teaching Hospital in Mosul between February and July (2006) and studied in the Department of Anatomy,College of Medicine,University of Mosul. Two groups of placentae were taken from the full tem pregnant women immediately after labour, each group consists of 10 placentae, the first group was obtained from healthy pregnant women (control group) while the second group was obtained from pregnant women with history of preeclampsia (10 patients).Results: the placental alkaline phosphatase enzyme is very important in trophoblastic transfer mechanism, this enzyme is abundant at term normal placenta. The human placenta contains this enzyme which is produced mainly by syncytiotropholast cells thus destruction of these cells which occurs in preeclampsia will lead to decrease in this enzyme activity and increase in degenerating acid phosphatase enzyme activity.Conclusion: there is a disturbance in the level of acid and alkaline phosphatase enzymes in the preeclamptic full term placentae.